Detutuhiya (Saling Menjatuhkan), Detiti'uwa (Saling Sikut): Membangun Ekosistem Ekonomi Berbasis Toleransi di Provinsi Gorontalo - Nasila, Rahmat; Dama, Desi Putri (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This study aims to analyze the level of tolerance among community groups in Gorontalo Province as well as its role in building a harmonious and sustainable local economic ecosystem. Important studies were conducted given that the foundation of tolerance was being threatened by the increasing symptoms of intolerance of the last few years. The research uses a qualitative approach with a single case study method against Gorontalo Province. Data collection was conducted through in-depth interviews, participatory observation, and document study. Data were analyzed inductively by triangulating the sources to guarantee their validity. Study results found the level of tolerance of the Gorontalo community in general is still quite high, yet faces serious challenges of increasing acts of intolerance. Tolerance is shown to contribute in strengthening social capital and creating productive local economic systems. Yet this foundation is vulnerable to collapse if intolerance becomes increasingly cultivated. Therefore, it is necessary to revitalize tolerance for the sake of maintaining social cohesion and a harmonious and just local economic ecosystem.